Evaluation of Integrated Digital Forensics Investigation Framework for the Investigation of Smartphones Using Soft System Methodology - Ruuhwan Ruuhwan; Imam Riadi; Yudi Prayudi (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The handling of digital evidence can become an evidence of a determination that crimes have been committed or may give links between crime and its victims or crime and the culprit. Soft System Methodology (SSM) is a method of evaluation to compare a conceptual model with a process in the real world, so deficiencies of the conceptual model can be revealed thus it can perform corrective action against the conceptual model, thus there is no difference between the conceptual model and the real activity. Evaluation on the IDFIF stage is only done on a reactive and proactive process stages in the process so that the IDFIF model can be more flexible and can be applied on the investigation process of a smartphone.